SERVICE GOODS DELIVERY SYSTEM DESIGN INFORMATION ON WIDRACIPTA LESTARI CV USING VISUAL BASIC6.0 - Eka Pratiwi; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
With existence of computerized system is expected that the existing service system at this time can be much faster to handle the problem of customer data and customer data searches, compared with manual service system.These enterprises can be run well, it is necessary to more important information such as customer lists, delivery destination list, price lists and other lists that are used for such business entity.With the existence of the necessary design in enterprise activities "Widracipta Lestari CV" will be shown a good impact at this time include, for making the next customer data stored in computer storage, shipping orders already in the customer data file data about shipping charges , So the cost is included in these efforts can be known through the Visual Basic 6.0 software.